2021
DOI: 10.15252/embj.2020107471
|View full text |Cite
|
Sign up to set email alerts
|

Loss of all three APP family members during development impairs synaptic function and plasticity, disrupts learning, and causes an autism‐like phenotype

Abstract: The key role of APP for Alzheimer pathogenesis is well established. However, perinatal lethality of germline knockout mice lacking the entire APP family has so far precluded the analysis of its physiological functions for the developing and adult brain. Here, we generated conditional APP/APLP1/APLP2 triple KO (cTKO) mice lacking the APP family in excitatory forebrain neurons from embryonic day 11.5 onwards. NexCre cTKO mice showed altered brain morphology with agenesis of the corpus callosum and disrupted hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 89 publications
2
41
0
Order By: Relevance
“…Previous studies showed that the perturbation of APP (and/or APLPs) induces severe cognitive deficits in mice ( 42 , 43 ). Specifically, forebrain GABAergic neuron-specific APP/APLP2 double-cKO mice exhibit impaired hippocampus-dependent spatial learning and memory ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that the perturbation of APP (and/or APLPs) induces severe cognitive deficits in mice ( 42 , 43 ). Specifically, forebrain GABAergic neuron-specific APP/APLP2 double-cKO mice exhibit impaired hippocampus-dependent spatial learning and memory ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…This may result from the functional redundancy of APP and APP-like proteins (APLP1 and ALPL2). In accordance, constitutive triple knockout mice (TKO) die after birth (Heber et al, 2000), whereas Nex-Cre cTKO (conditional triple KO in excitatory forebrain neurons starting during embryonic development) present gross brain morphology alterations (Steubler et al, 2021), showing a crucial role for APP family members during development. Our combination of in vitro silencing and acute interference of the APP C-terminal domain ex vivo , overcome a possible compensation by APP family members, while allowing to study APP specifically during postnatal developmental stages.…”
Section: Discussionmentioning
confidence: 99%
“…AICD-proteolytic products were shown to translocate to the nucleus where they can activate transcription factors and thus alter the synaptic function [83][84][85][86]. Indeed, APP itself, as well as its homologues and cleavage products, affect dendritic spine numbers [76,[87][88][89][90].…”
Section: Discussionmentioning
confidence: 99%